Writing reaction mechanisms in organic chemistry - Audrey Miller (Academic Press, 1992)
This book presents a review and practice of the fundamental principles that are useful tools in the writing of the mechanisms for organic reactions: It gives a step-by-step account of the bond reorganizations take place in the course of the reaction; it includes reactions of Nucleophiles and Bases, reactions involving Acids and other Electrophile. The book also covers Radicals and radical anions. Finally, the book discusses electrocyclic transformations, cycloadditions, sigmatropic reactions and the ene reaction